Sullo statuto costituzionale dell’emergenza. Ancora sul diritto pubblico come violenza o come funzione dei diritti della persona - Perfetti, Luca R. (P.A. Persona e Amministrazione, 2020)
L’emergenza pandemica ha reso più visibili processi già largamente in atto e destinati a non venire meno quando la pandemia sia superata. Poteri derogatori, organizzazioni ad hoc, anticipazione dell’emergenza al ricorrere di rischi ordinari e non di stretta necessità, estendersi di spazi di valutazione discrezionale sono tendenze largamente in atto da tempo. Da questo punto di vista, il dibattito sul regime costituzionale dell’emergenza finisce per approdare, da percorsi diversi, alla conclusione che essa si legittimi per via della salvezza dello Stato e dell’ordinamento. A fronte delle tendenze in atto e dei problemi che si manifestano, sembra invece necessario radicare il problema dell’emergenza – in linea con la tradizione del diritto europeo – nella sovranità e, poiché essa appartiene al popolo e la stessa autorità è resa interamente funzionale ai diritti inviolabili, il regime costituzionale dell’emergenza deve essere inteso come funzionale alla salvezza dei diritti fondamentali di fronte a pericoli imminenti e non alla salvezza dello Stato o in generale dell’autorità e del suo potere di comando. Emergency has become, in the past years, all ordinary. Covid-19 emergency revealed more clearly the large use of emergency in the legal system. The large use of emergency in the past years provide a wide range of legal means, mainly in via of exception and derogation. More specifically, Covid-19 emergency implement the various techniques, adding new measures, mainly to anticipate emergency measures based on risks instead of an actual or imminent risk, to appreciate emergency’s conditions in a discretionary fashion and with legal provision vague and unsubstantiated into the legislative decrees adopted to cope with the pandemic. In this critical situation, of derogations from normal human rights standards and alterations in the distribution of functions and powers among the different organs of the State, a discussion on constitutional status of emergency is mandatory. Italian academic writing during Covid-19 emergency seems unsatisfactory: Literature argued mainly in two – opposite – directions: under a positivistic perspective, Italian Constitution in force grounds emergency, as a way to conserve safety of the State and fundamental principles of the Republic; on the other hand, many scholars recurred to the traditional idea of ex facto oritur ius – therefore, facing extreme danger, facts grounds the State with powers either not by Law or under Constitution. The paper, maintain a positivistic approach and, under express constitutional rules on sovereignty – belonging to persons and recognizing fundamental rights as a component of people’s sovereignty – affirm Constitution grounds emergency powers as much as driven to human rights protection.